Yield and yield components of bread wheat as influenced by water stress, sowing date and cultivar in Sokoto, Sudan Savannah, Nigeria - Sokoto, Mohammed Bello; Singh, Agit (Scientific Research Publishing, 2013)
Field experiments were conducted during 2009/10 and 2010/2011 dry seasons at the Fadama Teaching and Research Farm of the Usmanu Danfodiyo University, Sokoto, in the Sudan Savanna ecological zone of Nigeria (latitude 13°01'N; longitude 5°15'E, altitude of 350 m above sea level) to study the effect of water stress, sowing date and cultivar on yield and yield components of wheat (Triticum aestivum L.). The treatments consisted of factorial combination of water stress at three critical growth stages which was imposed by withholding water at tillering, flowering, grain filling and control (no stress), four sowing dates (21st November, 5th December, 19th December and 2nd January) and two bread wheat cultivar (Star 11 TR 77173/SLM and Kuaz/Weaver), laid out in a split-plot design with three replications. Water stress and date of sowing were assigned to the main-plot, while variety was assigned to the sub-plots. Result revealed that water stress at tillering significantly reduced spike length and grains per spike. Whereas, water stress at flowering and grain filling significantly reduced 1000-grain weight, grain yield and harvest index. Results also indicated significant (P < 0.05) effect of sowing date on length of spike, spikelets per spike, grains per spike and grain yield. Early sown wheat significantly differed from the late sown wheat in all parameters measured. Yield and yield components decreased with delay in sowing date and it was highest at 21st November and 5th December and lowest at 19th December and 2nd January, therefore wheat should be sown in November or at least first week of December in this area and other area with similar climate. Variety had significant effect on spike per m-2, grain yield and harvest index. Water stress at flowering and grain filling should be avoided as they are the most critical growth stages in yield determination in wheat, because plants cannot recover, while delay in sowing resulted in reduction in yield and yield components. Star II TR 77173/SLM is therefore recommended for the area.